Identification of Haplotypes Associated With Resistance to Bacterial Cold Water Disease in Rainbow Trout Using Whole-Genome Resequencing - Liu, Sixin; Martin, Kyle E.; Gao, Guangtu; Long, Roseanna; Evenhuis, Jason P.; Leeds, Timothy D.; Wiens, Gregory D.; Palti, Yniv (Frontiers in Genetics, 2022)
Bacterial cold water disease (BCWD) is an important disease in rainbow trout aquaculture. Previously, we have identified and validated two major QTL (quantitative trait loci) for BCWD resistance, located on chromosomes Omy08 and Omy25, in the odd-year Troutlodge May spawning population. We also demonstrated that marker-assisted selection (MAS) for BCWD resistance using the favorable haplotypes associated with the two major QTL is feasible. However, each favorable haplotype spans a large genomic region of 1.3 - 1.6 Mb. Recombination events within the haplotype regions will result in new haplotypes associated with BCWD resistance, which will reduce the accuracy of MAS for BCWD resistance over time. The objectives of this study were 1) to identify additional SNPs (single nucleotide polymorphisms) associated with BCWD resistance using whole-genome sequencing (WGS); 2) to validate the SNPs associated with BCWD resistance using family-based association mapping; 3) to refine the haplotypes associated with BCWD resistance; and 4) to evaluate MAS for BCWD resistance using the refined QTL haplotypes. Four consecutive generations of the Troutlodge May spawning population were evaluated for BCWD resistance. Parents and offspring were sequenced as individuals and in pools based on their BCWD phenotypes. Over 12 million SNPs were identified by mapping the sequences from the individuals and pools to the reference genome. SNPs with significantly different allele frequencies between the two BCWD phenotype groups were selected to develop SNP assays for family-based association mapping in three consecutive generations of the Troutlodge May spawning population. Among the 78 SNPs derived from WGS, 77 SNPs were associated with BCWD resistance in at least one of the three consecutive generations. The additional SNPs associated with BCWD resistance allowed us to reduce the physical sizes of haplotypes associated with BCWD resistance to less than 0.5 Mb. We also demonstrated that the refined QTL haplotypes can be used for MAS in the Troutlodge May spawning population. Therefore, the SNPs and haplotypes reported in this study provide additional resources for improvement of BCWD resistance in rainbow trout.